The Influence of the Price of Shopee Account @hijabbyaida on Consumer Purchase Decisions in Kudus City - Aulia, Hana; Nastain, M.; Saputri, Dhea Octavia (PT FORMOSA CENDEKIA GLOBAL, 2025)
Currently, digital technology plays a crucial role in daily life, transforming theway people work, communicate, and obtain information. The digital era hascreated new opportunities in digital marketing, e-commerce, and tech startups. One business strategy in this era is using e-commerce platforms to accelerate business growth. This study examines the Shopee account @Hijabbyaida,focusing on the impact of pricing on consumer purchase decisions. Competitivepricing aligned with product quality can attract buyers. The research employs aquantitative method using questionnaires distributed to consumers of the Shopeeaccount @Hijabbyaida. The results show that price significantly influencespurchase decisions, with an r square value of 54.5%. Consumers tendto chooseproducts from @Hijabbyaida because the prices are deemed appropriate. This study concludes that proper pricing and attractive promotions on e-commerce platforms like Shopee can enhance consumer purchase decisions, sales, and customer satisfaction.